The frailty syndrome in general practitioner care - A pilot study - Drey, Michael; Wehr, H.; Wehr, Gritt; Uter, Wolfgang; Lang, Frieder; Rupprecht, Roland; Sieber, Cornel; Bauer, Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2011)
Background: Knowledge about frailty among patients seen by general practitioners (GP) is currently limited. Patients and methods: Frailty assessment by the criteria of Fried and additional documentation was performed at a GP’s office. Results: Out of 119 participating patients, 14.3% were classified as frail, 52.1% as prefrail, and 33.6% as not frail. Frailty was associated with comorbidity, the number of drugs prescribed, depressive symptoms, cognitive function, and frequency of falls. Conclusion: The prevalence of frailty is high among the cohort of elderly persons seen by a GP. Routine frailty assessment will help to direct preventive and therapeutic interventions.
Keywords: Frailty; Fried criteria; General practitioners; Elderly; Prevalence